NEUROPSYCHOLOGICAL DEVELOPMENT BIOPSYCHOSOCIAL VARIABLE IN INFANT AND CHILDREN WITH CONGENITAL HEART DISEASE: IDENTIFICATION OF PSYCHOLOGICAL MARKERS (Fiep Bulletin - online, 2012)
Introduction: You can understand that child development is a complex process and dependent on numerous factors. It is considered that the acquisition of new skills related to the age of the child and lived to interactions with other individuals of their social environment (Giron, 2005). Objective: To assessment behavioral expressions on the psychological development of children with congenital heart disease. Methodology: An observational study to characterize the neuropsychological development of children with and without congenital heart disease. Sample is composed of 261 children from zero to six years, divided into three groups: Group 1 (G1-observational) 87 children in clinical follow-up congenital heart disease before surgery, Group 2 (G2-observational) 87 children in clinical follow-up congenital heart disease Post-surgery and Group 3 (G3-contrast) 87 children without heart disease. For data collection a questionnaire will be used biopsychosocial and Development Screening Test II Denver. Results: The study is ongoing, and was referred to the research ethics committee, and takes place concurrently with sample characterization and composition of groups, observational and contrast. Are listed the key elements highlighted in the international literature in order to check with each group the main behavioral manifestations. Final considerations: The need for markers that can support the assessment process for safely and efficiently can define future approaches for the psychological intervention, supporting and advising thus the welfare of children with these diseases.
Keywords: neuropsychological development; biopsychosocial variables; congenital heart disease.